Direct laser writing of electronically conductive microstructures within soft hydrogel substrates - Lorenzo Lucherini; Veronica Navello; Outman Akouissi; Stéphanie P. Lacour; Esther Amstad (Materials Today Bio)
Hydrogels have emerged as promising materials for bioelectronic interfaces due to their tissue-like properties and high-water content. However, conventional hydrogels often suffer from poor electrical conductivity and mechanical stability, limiting their performance in long-term bioelectronic applications. Electronic conductivity can be imparted to hydrogels by functionalizing them with conductive particles. However, patterning of electronically conductive features within hydrogels remains challenging. Electronically conductive μm-sized patterns embedded in soft hydrogels would open up new possibilities to integrate hydrogel bioelectronics with electronic devices. Here, we introduce covalently crosslinked hydrogels with Young's moduli below 30 kPa that can be functionalized with metallic electronically conductive paths reaching an electronic conductivity up to (1505 ± 518) S cm−1. By tailoring the hydrogel substrate composition, we achieve writing fidelity up to ±5 %, with feature width as narrow as 5 μm. Using two-photon direct laser writing, we demonstrate the ability to pattern encapsulated conductive structures at the surface or within the bulk of the hydrogels. These patterned hydrogels offer new opportunities for creating soft, miniaturized bioelectronic interfaces, with potential applications in cellular and tissue electrophysiology.